X = 2
Y = -5
Step-by-step explanation:
We will multiply -7x + y=-19 by 3 so we can make the ys identical with the second equation. This way, its easier to eliminate them;
3(-7x + y=-19) =
-21x + 3y = -57
Then we can eliminate the ys by elimination. Be keen with the sign before each value;
-21x + 3y = -57
-
-2x + 3y =-19
=
-19x = - 38
X = -38 / -19
X = 2
We can substitute the value of x in one equation get the value of y;
-7(2) + y = -19
-14 + y = -19
Y = -19 +14
Y = -5
Learn More:
For more on solving equations by elimination check out;
https://brainly.com/question/11155931
#LearnWithBrainly